A framework for whole lifecycle cost of long-term digital preservation - Badawy, Mohammed Abdel Salam Abdel Azim (Cranfield University, 2017)
Digital preservation, also known as digital curation, is the active management of digital information, over time, to ensure its accessibility and usability. Digital preservation is nowadays an active area of research, for many reasons: the rapid evolution of technology, which also results in the rapid obsolescence of old technologies; degradation of physical records; constantly increasing volumes of digital information and, importantly, the fact that it has started to become a legal obligation in many countries. This research project aims to develop an innovative framework estimate costs of long term digital preservation. The framework can lead to generating a cost model that quantifies costs within different business sectors, while capturing the impact of obsolescence and uncertainties on predicted cost. Case studies from financial, healthcare and clinical trials sectors are used to prove the framework concept. Those sectors were chosen because between them they share all file types that are required to be preserved and all are either obliged by European or local laws, e.g. EU Data Retention Directive (2006/24/EC) and/or UK Data Retention Regulations 2014 No. 2042, or interested in preserving their digital assets. The framework comprises of three phases: assessing digital preservation activities, cost analysis and expansion and cost estimation. The framework has integrated two processes that will enable the user to reach a more accurate cost estimate; a process for identifying uncertainties with digital preservation activities and a cost modelling process. In the framework cloud computing was used as an example for storage and compute technologies. Combining different research methodology techniques was used in this research project. Starting with conducting a thorough literature review covering digital preservation and cost modelling. Following the literature review; is a combination qualitative and quantitative approaches, using semi-structured interview technique to collect data from industry experts. Industry experts were chosen from companies, firms and government bodies working with or researching digital preservation. Finalising with validating results by real-life case studies from businesses in selected sectors and experts’ verdict. Comparing the output of the framework to real-life case studies, demonstrated how companies/firms, who target to preserve their digital assets, can utilise it to predict accurately future costs for undertaking such investment. By applying industrially-based cost modelling approaches the framework generates a cost model that predicts single-point and three-points cost estimates, an obsolescence taxonomy, uncertainties identification process and quantifying uncertainties and obsolescence impact on cost prediction. Providing decision makers with all the framework outputs, will provide them with quantifiable information about their future investment, while remaining clear to understand and easy to amend. This makes the framework provide long-term total cost prediction solution for digital preservation to firms; helping, guiding and adding insight into digital preservation added value.
Keywords: Cost estimation; cost modelling; digital curation; uncertainty cost; obsolescence cost; obsolescence taxonomy